Answer:
Part a)
[tex]KE = 1.83 \times 10^7 J[/tex]
Part b)
[tex]KE = 7.92 \times 10^7 J[/tex]
Explanation:
Here by energy conservation we can say
initial total energy = final total energy
now we have
[tex]-\frac{Gm_1m_2}{r_1} + \frac{1}{2}mv_1^2 = -\frac{Gm_1m_2}{r_2} + \frac{1}{2}mv_2^2[/tex]
now we have
[tex]-\frac{(6.67\times 10^{-11})(5.7 \times 10^{23})(10)}{3\times 10^6} + 5 \times 10^7 = -\frac{(6.67 \times 10^{-11})(5.7 \times 10^{23})(10)}{4 \times 10^6} + KE[/tex]
now we have
[tex]KE = 1.83 \times 10^7 J[/tex]
Part b)
Now again at maximum height the final kinetic energy will be zero
so we have
[tex]-\frac{Gm_1m_2}{r_1} + \frac{1}{2}mv_1^2 = -\frac{Gm_1m_2}{r_2} + \frac{1}{2}mv_2^2[/tex]
now we have
[tex]-\frac{(6.67\times 10^{-11})(5.7 \times 10^{23})(10)}{3\times 10^6} + KE = -\frac{(6.67 \times 10^{-11})(5.7 \times 10^{23})(10)}{8 \times 10^6} + 0[/tex]
now we have
[tex]KE = 7.92 \times 10^7 J[/tex]